Generation of two induced pluripotent stem cells lines from a Mucopolysaccharydosis IIIB (MPSIIIB) patient - Sara Vallejo-Diez (Stem Cell Research, 2018)
Mucopolysaccharydosis IIIB is the second most frequent form of Sanfilippo syndrome, a degenerative, pediatric lysosomal storage disease (LSD) characterized by severe neurological disorders and death. We have generated two iPSCs lines derived from dermal fibroblast from a MPSIIIB homozygous (P358L) donor. Cells were reprogrammed with OriP/EBNA1-based episomal plasmids containing: OCT3/4, SOX2, KLF4, L-MYC, LIN28, BCL-xL and shp53. Both cell lines are homozygous for the P358L mutation of the α-N-acetylglucosaminidase (NAGLU) gene, have normal karyotype, are free of plasmid integration, express high levels of pluripotency-associated markers and can differentiate into the three germ layers. Resource table: Unlabelled TableUnique stem cell lines identifierIMEDEAi005-AIMEDEAi005-BAlternative names of stem cell linesiPS GM02931 CL2 (IMEDEAi005-A)iPS GM02931 CL3 (IMEDEAi005-B)InstitutionIMEDEA - Instituto Mediterráneo de Estudios AvanzadosContact information of distributorDaniel Bachiller; d.b@csic.esType of cell linesiPSCsOriginHumanCell SourceOriginal cell type: GM02931 Fibroblast from the Coriell InstituteClonalityClonal cell linesMethod of reprogrammingEpisomal Plasmids (Klf4, Sox2, Oct4, shp53, L-Myc, Lin28, Bcl-xL)Multiline rationaleSame disease, isogenic cell linesGene modificationNOType of modificationN/AAssociated diseaseMucopolysaccharidosis, Type IIIB; MPS3B(MPS IIIB; OMIM entry # 252920)Gene/locusNAGLU 17q21.2Method of modificationN/AName of transgene or resistanceN/AInducible/constitutive systemN/ADate archived/stock date26/09/2018Cell line repository/bankRegistered in the Human Pluripotent Stem Cell Registry (https://hpscreg.eu).Ethical approvalOriginal line (GM02931 Fibroblast) has been obtained by Coriell Institute for Medical Research. Regarding policy of informed consent form, the Coriell Institute for Medical Research, which operates the NIGMS Human Genetic Cell Repository, has obtained a Certificate of Confidentiality from the National Institutes of Health to help ensure patient's privacy. Resource utility: Although the generation of iPSCs has been reported for some lysosomal storage diseases (LSD) in general, and from other mutations of the NAGLU gene in particular (Lemonnier et al., 2011), this is the first time that NAGLU Pro358Leu MPSIIIB-iPSCs lines have been generated and fully characterized demonstrating their quality as iPS cells. Resource details: Mucopolysaccharidosis IIIB (MPSIII, Sanfilippo syndrome type B) is a pediatric neurodegenerative disorder caused by a deficiency in NAGLU, an enzyme required for lysosomal degradation of heparin sulphate (HS). When the enzyme is absent or malfunctioning, HS accumulates in the cells of several tissues, with devastating effects in the brain and central nervous system. MPSIIIB is inherited in an autosomal recessive manner and presents an incidence between 0.03 and 0.78 cases per 1 × 105 live births (Fedele, 2015) depending on the country. Currently there is no therapy available.The NAGLU gene was identified in 1996, is located on chromosome 17q21.1 and contains 6 exons. More than 150 NAGLU mutations have been reported, being most of them missense (Valstar et al., 2010). All of them lead to MPSIIIB but, unlike MPSIIIA, none is predominant.The two iPSCs lines described in this report, IMEDEAi005-A and IMEDEAi005-B, (See Table 1) were generated from skin fibroblast obtained from a clinically affected homozygous donor. The mutant allele consists on a C > T transversion at nucleotide 1073 (1073 > T) resulting in a substitution of leucine for proline at codon 358 (Pro358Leu).Skin fibroblasts were reprogrammed to iPSCs by nucleofection with four OriP/EBNA1 (Epstein-Barr nuclear antigen-1) based episomal plasmids encoding 5 reprogramming genes (OCT3/4, SOX2, KLF4, L-Myc, LIN28 and BCL-xL), in addition to a short hairpin RNA against p53. The iPSCs lines showed morphology (Fig. 1A) and growth behaviour typical of human Embryonic Stem Cells (hESC), as well as normal female karyotype (46, XX) (Fig. 1B). After 12 passages, PCR analysis confirmed that both iPSCs lines had completely lost the episomal vectors (Fig. 1C). The identity of iPS cells and their parental fibroblasts was confirmed by STR analysis (Table 2, data not shown) in addition to the identification of the disease-associated mutation in the NAGLU gene by DNA sequencing (Fig. 1D). Regarding the iPSC phenotype, both lines expressed the pluripotency-associated markers: OCT3/4, NANOG, SOX2 and TRA-1-60 (Fig. 1E), and TRA-1-81 quantified by flow cytometry (Fig. 1G), resulting in 88.17% and 83.4% of TRA-1-81 positive cells in IMEDEAi005-A and IMEDEAi005-B respectively. Finally, the differentiation capacity of iPSCs lines was analyzed by embryoid body (EBs) formation. Expression of markers specific of the three germ layers was observed after at least 10 days of spontaneous differentiation (Fig. 1F). Mycoplasma analysis was negative for both iPSCs lines (Supplementary Fig. S1).Skin fibroblasts were reprogrammed to iPSCs by nucleofection with four OriP/EBNA1 (Epstein-Barr nuclear antigen-1) based episomal plasmids encoding 5 reprogramming genes (OCT3/4, SOX2, KLF4, L-Myc, LIN28 and BCL-xL), in addition to a short hairpin RNA against p53. The iPSCs lines showed morphology (Fig. 1A) and growth behaviour typical of human Embryonic Stem Cells (hESC), as well as normal female karyotype (46, XX) (Fig. 1B). After 12 passages, PCR analysis confirmed that both iPSCs lines had completely lost the episomal vectors (Fig. 1C). The identity of iPS cells and their parental fibroblasts was confirmed by STR analysis (Table 2, data not shown) in addition to the identification of the disease-associated mutation in the NAGLU gene by DNA sequencing (Fig. 1D). Regarding the iPSC phenotype, both lines expressed the pluripotency-associated markers: OCT3/4, NANOG, SOX2 and TRA-1-60 (Fig. 1E), and TRA-1-81 quantified by flow cytometry (Fig. 1G), resulting in 88.17% and 83.4% of TRA-1-81 positive cells in IMEDEAi005-A and IMEDEAi005-B respectively. Finally, the differentiation capacity of iPSCs lines was analyzed by embryoid body (EBs) formation. Expression of markers specific of the three germ layers was observed after at least 10 days of spontaneous differentiation (Fig. 1F). Mycoplasma analysis was negative for both iPSCs lines (Supplementary Fig. S1).In conclusion, we have successfully generated and characterized, for the first time to our knowledge, two human iPSCs lines from a MPSIIIB donor homozygous for the P358L NAGLU mutation. The new lines will complement the existing murine MPS IIIB model, with their potential to be used in a development of a purely human in vitro model of the disease.